The ex officio annulment of a judgment for alleged deficiency of evidence (Revista do Tribunal Regional Federal da 3ª Região, 2021)
This article proposes a critical analysis of the ex officio annulment of a judgment due to alleged evidentiary deficiencies, in conjunction with the rules and principles governing civil procedure.
Keywords: Judgment; ex officio annulment; evidentiary deficiency; instructional powers of the judge; dispositive principle